How Does Triple Bottom Line Reporting Influence Financial Performance? (Evidence from the LQ45 Companies Listed in the Indonesia Stock Exchange) - Suttipun, Muttanachai; Setyadi, Dimas Aryo (ABAC ODI JOURNAL Vision. Action. Outcome, 2017)
Abstract The objectives of this study are to investigate the extent of triple bottom line (TBL) reporting in the annual reports of companies listed in the Indonesia Stock Exchange, and to test for the influence of corporate characteristics and the level of TBL reporting on financial performance. The population is the LQ45 group of companies listed in the Indonesia Stock Exchange. The study considers the corporate annual reports issued during the period 2011 to 2013. The results show that Indonesian listed companies provided an average of 932 sentences of TBL reporting in their annual reports during the period 2011 to 2013. There is a significant positive influence of the levels of TBL reporting and the type of industry on corporate financial performance. Among previous studies on corporate social responsibility reporting in Indonesia, this study is the first to investigate TBL reporting by Indonesian listed companies. Key Words: Triple Bottom Line reporting, LQ45, financial performance, and the Indonesia Stock Exchange